Virulence Biomarkers of Bursaphelenchus xylophilus: A Proteomic Approach - Cardoso, Joana M. S.; Anjo, Sandra I.; Manadas, Bruno; Silva, Hugo; Abrantes, Isabel; Nakamura, Katsunori; Fonseca, Luís (Frontiers in Plant Science, 2022)
The pinewood nematode (PWN), Bursaphelenchus xylophilus, one of the most serious forest pests worldwide, is considered the causal agent of the pine wilt disease (PWD). The main host species belong to the genus Pinus and a variation in the susceptibility of several pine species to PWN infection is well-known. It is also recognized that there is variation in the virulence among B. xylophilus isolates. In the present study, we applied a quantitative mass spectrometry-based proteomics approach to perform a deep characterization of proteomic changes across two B. xylophilus isolates with different virulence, from different hosts and geographical origins. A total of 1456 proteins were quantified and compared in the two isolates secretomes and a total of 2741 proteins were quantified and compared in the nematode proteomes in pine tree extract and fungus stimuli conditions. From the proteomic analyses, a group of proteins was selected and identified as potential virulence biomarkers and shed light on putative most pathogenic proteins of this plant-parasitic nematode. Proteomic data are available via ProteomeXchange with identifier PXD029377.